Mechanical induction of labor and ecbolic-less vaginal birth after cesarean section: A cohort study - Hytham Atia; Mohamed Ellaithy; Ahmed Altraigey; Mohamed Kolkailah; Amal Alserehi; Shabana Ashfaq (Elsevier, 2018)
Objective: During delivery counseling, some women with previous uncomplicated cesarean section (CS) wish mechanical induction of labor (IOL) but they are not accepting the added risk of using ecbolics to induce and/or augment labor. The objective of the study was to assess the safety and efficacy of the isolated use of transcervical Foley's catheter balloon as a mean of mechanical cervical ripening (CR)/IOL and successful ecbolic-less vaginal birth after cesarean section (VBAC). Materials and methods: A cohort study was conducted in two tertiary care maternity hospitals between October 2013 and July 2016 and recruited women with singleton pregnancy and cephalic presentation who had previous one uncomplicated CS and were scheduled for mechanical CR/IOL at term for routine obstetric indications. No ecbolics were used for induction or augmentation of labor as per patients' request. The primary outcome variable was the rate of successful VBAC. Results: 108 Women had a completed trial of mechanical CR/IOL without ecbolics till delivery. Active labor started in 94 women (87%), however only 43 women (39.8%) had successful VBAC. No woman in the study cohort had uterine rupture, scar dehiscence, uterine tachysystole, postpartum hemorrhage and/or puerperal sepsis. No cases were admitted to intensive care units and there were no maternal mortalities. Prior successful VBAC and post-expulsion BS were the only independent predictors for successful VBAC and shorter duration of labor after balloon expulsion. Conclusion: Mechanical IOL with the mere use of transcervical Foley's catheter is a safe and effective method of VBAC in women refusing use of ecbolics.